(-y)-y=3

Simple and best practice solution for (-y)-y=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-y)-y=3 equation:



(-y)-y=3
We move all terms to the left:
(-y)-y-(3)=0
We add all the numbers together, and all the variables
(-1y)-y-3=0
We add all the numbers together, and all the variables
-1y+(-1y)-3=0
We get rid of parentheses
-1y-1y-3=0
We add all the numbers together, and all the variables
-2y-3=0
We move all terms containing y to the left, all other terms to the right
-2y=3
y=3/-2
y=-1+1/2

See similar equations:

| x+9=−14 | | 6x+2x=3x17 | | 17^e=1/2 | | 20^e=400 | | 5+k/4=12 | | 33/44=3/x | | 5x-10/5=x+10 | | 42+5t=87 | | 7x-0.5x-4=2x+17 | | 3/51=1/x | | −23x–214=274x=502 | | 12/x=36/51 | | 0.6x+0.3x=7.2 | | 2.5x+0.5x=-12 | | 22n=19 | | 5(2x+15)=145 | | 7m=–7+6m | | h/11-7=0 | | 2=3c-3 | | 2x+6=x+(-4) | | 25=f−27 | | h+50=87 | | q+16=51 | | s+6=95 | | 11=9-2(p-3) | | 20.9y=-250.8 | | 15w+2=30+20w | | 3+2m=5.6 | | 6=b/2-4 | | 12xx-6=30 | | –8(–6+7m)= | | 12=3/c |

Equations solver categories